2023
DOI: 10.3390/plants12223834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerated Drip Irrigation and Nitrogen Application on Soil Properties, Soil Bacterial Communities and Agronomic Traits of Cucumber in a Greenhouse System

Zheyuan Xiao,
Hongjun Lei,
Yingji Lian
et al.

Abstract: Root hypoxia stress and soil nutrient turnover have been related to reduced crop productivity. Aerated drip irrigation (ADI) can effectively enhance crop productivity and yield. However, the response of the soil bacterial community to different irrigation water dissolved oxygen (DO) concentrations remains elusive due to the extreme sensitivity of microorganisms to environmental variations. We investigated the effects of aerated irrigation with different concentrations of DO on soil properties and agronomic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Thus, the present study revealed some differences relative to prior reports with respect to the characteristics of monocropping and intercropping systems, while also providing new details regarding the effects of different levels of nitrogen application under these conditions. Bradyrhizobium is capable of utilizing plant-derived carbohydrates to exchange fixed nitrogen, whereas Nitrospira bacteria with nitrifying activity are capable of converting soil ammonia nitrogen into nitrate nitrogen to maintain soil nitrogen cycling [55,56]. As nitrogen fertilizer levels rose, Bradyrhizobium abundance under monocropping conditions declined, while Nitrospira abundance increased and decreased in the monocropping and intercropping systems, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study revealed some differences relative to prior reports with respect to the characteristics of monocropping and intercropping systems, while also providing new details regarding the effects of different levels of nitrogen application under these conditions. Bradyrhizobium is capable of utilizing plant-derived carbohydrates to exchange fixed nitrogen, whereas Nitrospira bacteria with nitrifying activity are capable of converting soil ammonia nitrogen into nitrate nitrogen to maintain soil nitrogen cycling [55,56]. As nitrogen fertilizer levels rose, Bradyrhizobium abundance under monocropping conditions declined, while Nitrospira abundance increased and decreased in the monocropping and intercropping systems, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Aerated drip irrigation (ADI) technology delivers micro-nano bubble water through the SDI system to the root zone to a certain extent, alleviating the problem of root anoxia caused by conventional SDI. Some studies have shown that aerated irrigation significantly affects the inter-root soil oxygen environment of crops, enhancing soil permeability, improving soil enzyme activity and the activities of soil microorganisms [ 13 , 14 ], promoting the aerobic respiration of the crop root system [ 15 ], and increasing crop yields and fruit quality [ 16 ]. Soil aeration increases the crop yield and improves the quality of cucumber, potato, zucchini, and rice [ 11 ].…”
Section: Introductionmentioning
confidence: 99%